2016
DOI: 10.18632/oncotarget.10311
|View full text |Cite
|
Sign up to set email alerts
|

EphrinA4 plays a critical role in α4 and αL mediated survival of human CLL cells during extravasation

Abstract: A role of endothelial cells in the survival of CLL cells during extravasation is presently unknown. Herein we show that CLL cells but not normal B cells can receive apoptotic signals through physical contact with TNF-α activated endothelium impairing survival in transendothelial migration (TEM) assays. In addition, the CLL cells of patients having lymphadenopathy (LApos) show a survival advantage during TEM that can be linked to increased expression of α4 and αL integrin chains. Within this context, ephrinA4 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Moreover, signaling by Rac1 and CDC42 GTPases which activates LFA-1 shows extensive degrees of alteration in CLL patients, so that some authors suggest that progression to CLL requires these GTPases to be bypassed [ 63 ]. Defective LFA-1-dependent endothelial transmigration could play a role in the survival of CLL cells [ 64 ]. Despite the necessity of B-CLL cells to home in on lymph nodes and bone marrow, it is not uncommon to observe a lower CD18 expression in B-CLL than in normal B cells in healthy individuals [ 60 ].…”
Section: Inside-out Signaling By Lfa-1mentioning
confidence: 99%
“…Moreover, signaling by Rac1 and CDC42 GTPases which activates LFA-1 shows extensive degrees of alteration in CLL patients, so that some authors suggest that progression to CLL requires these GTPases to be bypassed [ 63 ]. Defective LFA-1-dependent endothelial transmigration could play a role in the survival of CLL cells [ 64 ]. Despite the necessity of B-CLL cells to home in on lymph nodes and bone marrow, it is not uncommon to observe a lower CD18 expression in B-CLL than in normal B cells in healthy individuals [ 60 ].…”
Section: Inside-out Signaling By Lfa-1mentioning
confidence: 99%
“…Additionally, soluble ephrinA4 isolated from the sera of patients led to an increase in the number and viability of CLL cells recovered from the LNs of adoptively transferred mice. Overall, these results indicate that ephrinA4-mediated survival during TEM could enhance the transcellular TEM route of the CLL cells [167].…”
Section: Leukemias Of Lymphoid Originmentioning
confidence: 60%
“…Moreover, signaling by Rac1 and CDC42 GTPases to activate LFA-1 shows extensive degrees of alteration in CLL patients, so that some authors suggested that progression to CLL requires bypassing these GTPases [38]. The defective LFA1-dependent endothelial transmigration could play a role in survival of CLL cells [39]. Despite the necessity of CLL B cells to home to lymph nodes and bone marrow, it is not uncommon to observe a lower CD18 expression in B-CLL than that of normal B cells in healthy individuals [35].…”
Section: Lfa-1 In Chronic Lymphocytic Leukemiamentioning
confidence: 99%